Qualitative Assessment of MWCNT- Treated Grains of Some Food Cereals: Life Sciences-Botany - Joshi, Anjali; Thakur, Neha; Verma, Gaurav; Kumar, Avneesh; Kumar, Vajinder; Yadav, Narender; Kaur, Simranjeet (International Journal of Life Science and Pharma Research, 2022)
Abstract: The advancement in nanotechnology and its utilisation in agriculture increases agricultural output. To protect crops from numerous plant diseases and pests, excessive chemical, pesticide, and fungicide use can be replaced with nanoparticles. The first step of plant growth, seed germination, is thought to be the most delicate time in a plant's life cycle. The effects of carbon nanotubes on seed quality and seed content both before and after treatment are discussed in this study. Rice, wheat, and oat grains were compared with the seeds harvested from MWCNT (multiwalled carbon nanotubes) treated plants at three different concentrations (70, 80, and 90μg/ml) and indicated no significant changes in various components such as carbohydrates, protein, crude fat, crude fibre, moisture and ash contents when compared to untreated grains. Grain primed with MWCNT before sowing resulted in no change in the above components, but an increase in mineral accumulation was found. Here, we noticed a significant increase in grain yield. The treatment of MWCNT enhanced the growth of grains count by two folds compared to the control plant. The wheat grain had a moisture content: 9.3-9.38%, ash content: 1.31-1.35%, crude fat: 0.9-0.93%, crude fibre: 1.1-1.13%, protein content: 9.2-9.38%, carbohydrate content: 77.96-78.04%. The rice grain had a moisture content: 9.98-10.25%, ash content: 0.42-0.45%, crude fat: 1.00-1.02%, crude fibre: 0.9-0.93%, protein content: 4.42-4.49%, carbohydrate content: 82.92-83.03%. The oat grain had a moisture content: 8.95-9.3%, ash content: 1.74-1.8%, crude fat: 2.1-2.3%, crude fibre: 5.1-5.27%, protein content: 9.5-9.59%, carbohydrate content: 71.78-72.23%. The study revealed that the examined MWCNT concentrations might efficiently enhance the grain yield without altering the grain quality.